Design and synthesis of ternary-component layered double hydroxides for high-performance supercapacitors: understanding the role of trivalent metal ions. (20th January 2017) - Wang, Xin; Lin, Yinyin; Su, Yan; Zhang, Bing; Li, Cunjun; Wang, Hai; Wang, Linjiang
Graphical abstract: The two critical characteristics of the ultrathin nanosheets and compositional tunable crystal structure of NiCoM(M = Al, Fe)-LDH in the design and synthesis electrodes for supercapacitors. Abstract: To understand the insightful mechanics of the effects of the trivalent metal ions on the electrochemical performance of ternary-component layered double hydroxides (LDH), the ternary LDH composed by NiCoAl-LDH, NiCoAl0.5 Fe0.5 -LDH and NiCoFe-LDH are designed, synthesized and characterized. Despite bivalent metal ions (Ni 2+, Co 2+ ) having been demonstrated to play a highly specialized role in surface redox chemistry, the role of the trivalent metal ions within the metal hydroxide layer has not been elucidated yet in supercapacitor applications. Here we demonstrated that Al 3+ has a positive effect on the stabilization of host layers of LDH, which leads to the improvement of the electrochemical performance. It was also found that Al 3+ could regulate the crystallinity, hydrophilicity and nanosheets stacking of LDH. Further, comparative studies show that NiCoAl-LDH exhibited superior specific capacitance of 1153 F g −1 at 6 A g −1, and excellent cycling stability (ca. 92.97% capacitance retention after 3000 cycles). We attribute such remarkable enhancement in cyclic performance to the framework stability of Al 3+ in the multi-metal LDH matrix layer. These results highlight the importance of trivalent metal ions in ternary-component LDH for high-performance supercapacitors and may guide future design and synthesis of LDH.